2008
DOI: 10.1177/0269215507080141
|View full text |Cite
|
Sign up to set email alerts
|

A study of constraint-induced movement therapy in subacute stroke patients in Hong Kong

Abstract: Significant improvement in hand function could be achieved with constraint-induced movement therapy in subacute stroke patients, which was maintained up to 12 week follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 37 publications
5
65
0
7
Order By: Relevance
“…[22][23][24] The resource-intensive programme with individual patient-therapist interaction for 60 hours in two weeks [22][23][24] was more extensive, intense and focused on upper limb training than our experimental intervention. Two recent reports compared groups with similar amounts and intensities of training 25,26 and achieved better results with the constraint-induced movement therapy approach. On the other hand, they did not use equal contents of training in their study groups.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] The resource-intensive programme with individual patient-therapist interaction for 60 hours in two weeks [22][23][24] was more extensive, intense and focused on upper limb training than our experimental intervention. Two recent reports compared groups with similar amounts and intensities of training 25,26 and achieved better results with the constraint-induced movement therapy approach. On the other hand, they did not use equal contents of training in their study groups.…”
Section: Discussionmentioning
confidence: 99%
“…Tables 1 and 2 summarize the finding from our review on CIMT and mCIMT, respectively. We found 4 articles [23][24][25][26]28], describing results following the use of CIMT (Table 1) and 4 article [28][29][30][31] describing results following the use of mCIMT in patients with chronic stroke ( Table 2) that met our criteria. The total number of subjects (patients and normal subjects) in each study varied from 7 to 222 and from 17 to 35 in CIMT and mCIMT, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Such Understanding for this relationship would add more in-depth insights on the functional relevance of plastic brain changes in stroke following CIMTs to optimize the field of neuro-rehabilitation [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…11 In the case of CIMT specifically, a trial involving people 2-12 weeks poststroke found that UE function improved more with CIMT than with dose-matched usual care. 12 Nonetheless, Brunner and colleagues recommended postponing implementation of CIMT until 1 month after stroke because substantial improvement in UE function occurs in response to standard rehabilitation within the first month. 13 At 4 weeks post-stroke, therefore, PF seemed well positioned to benefit from CIMT.…”
Section: The Evidencementioning
confidence: 99%